Dermatoses bolhosas auto-imunes - Cunha, Paulo R.; Barraviera, Silvia Regina Catharino Sartori [UNESP] (FapUNIFESP (SciELO), 2009)
Autoimmune bullous dermatoses are diseases in which blisters and vesicles are the primary and fundamental types of skin lesion. Their classification is based on the location of the blister: intraepidermal and subepidermal. Patients produce autoantibodies against self-specific structures of the skin detectable by immunofluorescence techniques, immunoblotting and ELISA. Recent advances in molecular and cellular biology have brought to knowledge these self-antigens, against which patients are sensitized, and which are found in epidermis or in the dermo-epidermal junction. These are low incidence, but high morbidity diseases that may be fatal. The aim of this article is to review and describe the progress of four autoimmune vesiculobullous disorders: endemic pemphigus foliaceous (wild fire), pemphigus vulgaris, bullous pemphigoid and dermatitis herpetiformis. ©2009 by Anais Brasileiros de Dermatologia.
Autoimmune bullous dermatoses
Keywords: Allergy and immunology; Bullous pemphigoid; Dermatitis herpetiformis; Pemphigus; Skin diseases vesiculobullous; antibiotic agent; antigen; antiparasitic agent; autoantibody; azathioprine; chloroquine; cyclophosphamide; cyclosporin; dapsone; immunoglobulin; methotrexate; methylprednisolone; mycophenolic acid 2 morpholinoethyl ester; nicotinamide; prednisone; riboflavin; rituximab; sulfone; tetracycline; bacterial infection; blister; bullous pemphigoid; chill; clinical classification; clinical feature; dermatitis herpetiformis; diet therapy; drug dose reduction; endemic disease; enzyme linked immunosorbent assay; epidermis; fever; gluten free diet; headache; histopathology; human; hypotension; immunoblotting; immunofluorescence; incidence; knowledge; morbidity; nausea; pathogenesis; pemphigus foliaceus; pemphigus vulgaris; plasmapheresis; pruritus; review; skin defect; skin sensitization; strongyle infection; treatment duration; treatment response; urticaria; Autoantibodies; Autoantigens; Autoimmune Diseases; Dermatitis Herpetiformis; Enzyme-Linked Immunosorbent Assay; Fluorescent Antibody Technique; Humans; Immunoblotting; Pemphigoid, Bullous; Skin Diseases, Vesiculobullous